Fevipiprant, a prostaglandin D2 receptor 2 antagonist, in patients with persistent eosinophilic asthma: a single-centre, randomised, double-blind, parallel-group, placebo-controlled trial. Issue 9 (September 2016) - Gonem, Sherif; Berair, Rachid; Singapuri, Amisha; Hartley, Ruth; Laurencin, Marie F M; Bacher, Gerald; Holzhauer, Björn; Bourne, Michelle; Mistry, Vijay; Pavord, Ian D; Mansur, Adel H; Wardlaw, Andrew J; et al.
Summary: Background: Eosinophilic airway inflammation is often present in asthma, and reduction of such inflammation results in improved clinical outcomes. We hypothesised that fevipiprant (QAW039), an antagonist of prostaglandin D2 receptor 2, might reduce eosinophilic airway inflammation in patients with moderate-to-severe eosinophilic asthma. Methods: We performed a single-centre, randomised, double-blind, parallel-group, placebo-controlled trial at Glenfield Hospital (Leicester, UK). We recruited patients with persistent, moderate-to-severe asthma and an elevated sputum eosinophil count (≥2%). After a 2-week single-blind placebo run-in period, patients were randomly assigned (1:1) by the trial pharmacist, using previously generated treatment allocation cards, to receive fevipiprant (225 mg twice per day orally) or placebo, stratified by the use of oral corticosteroid treatment and bronchoscopy. The 12-week treatment period was followed by a 6-week single-blind placebo washout period. The primary outcome was the change in sputum eosinophil percentage from baseline to 12 weeks after treatment, analysed in the intention-to-treat population. All patients who received at least one dose of study drug were included in the safety analyses. This trial is registered withClinicalTrials.gov, numberNCT01545726, and with EudraCT, number 2011-004966-13. Findings: Between Feb 10, 2012, and Jan 30, 2013, 61 patients were randomly assigned to receive fevipiprant (n=30) or placebo (n=31). Three patients in the fevipiprant group and four patients in the placebo group withdrew because of asthma exacerbations. Two patients in the fevipiprant group were incorrectly given placebo (one at the mid-treatment visit and one throughout the course of the study). They were both included in the fevipiprant group for the primary analysis, but the patient who was incorrectly given placebo throughout was included in the placebo group for the safety analyses. Between baseline and 12 weeks after treatment, sputum eosinophil percentage decreased from a geometric mean of 5·4% (95% CI 3·1–9·6) to 1·1% (0·7–1·9) in the fevipiprant group and from 4·6% (2·5–8·7) to 3·9% (CI 2·3–6·7) in the placebo group. Compared with baseline, mean sputum eosinophil percentage was reduced by 4·5 times in the fevipiprant group and by 1·3 times in the placebo group (difference between groups 3·5 times, 95% CI 1·7–7·0; p=0·0014). Fevipiprant had a favourable safety profile, with no deaths or serious adverse events reported. No patient withdrawals were judged by the investigator to be related to the study drug. Interpretation: Fevipiprant reduces eosinophilic airway inflammation and is well tolerated in patients with persistent moderate-to-severe asthma and raised sputum eosinophil counts despite inhaled corticosteroid treatment. Funding: Novartis Pharmaceuticals, AirPROM project, and the UK National Institute for Health Research.